Oral Health-Related Quality of Life of Adult Orang Asli in Jelebu, Malaysia: A Cross-Sectional Study - Wan Mohamad Nasir Wan Othman; Wan Nur Alwani Wan Abdul Aziz; Wan Nor Syariza Wan Ali; Haslinda Ramli; Muslimah Ithnin (2024)
Indexed by WOS/Scopus/ERA